Outcomes of Decompressive Surgery for Patients With Severe Cerebral Venous Thrombosis: DECOMPRESS2 Observational Study - Aaron, Sanjit; Ferreira, Jorge M.; Coutinho, Jonathan M.; Canhão, Patrícia; Conforto, Adriana B.; Arauz, Antonio; Carvalho, Marta; Masjuan, Jaime; Sharma, Vijay K.; Putaala, Jukka; Uyttenboogaart, Maarten; Werring, David J.; et al. (Wolters Kluwer, 2024)
BACKGROUND: Decompressive neurosurgery is recommended for patients with cerebral venous thrombosis (CVT) who have large parenchymal lesions and impending brain herniation. This recommendation is based on limited evidence. We report long-term outcomes of patients with CVT treated by decompressive neurosurgery in an international cohort. METHODS: DECOMPRESS2 (Decompressive Surgery for Patients With Cerebral Venous Thrombosis, Part 2) was a prospective, international cohort study. Consecutive patients with CVT treated by decompressive neurosurgery were evaluated at admission, discharge, 6 months, and 12 months. The primary outcome was death or severe disability (modified Rankin Scale scores, 5–6) at 12 months. The secondary outcomes included patient and caregiver opinions on the benefits of surgery. The association between baseline variables before surgery and the primary outcome was assessed by multivariable logistic regression. RESULTS: A total of 118 patients (80 women; median age, 38 years) were included from 15 centers in 10 countries from December 2011 to December 2019. Surgery (115 craniectomies and 37 hematoma evacuations) was performed within a median of 1 day after diagnosis. At last assessment before surgery, 68 (57.6%) patients were comatose, fixed dilated pupils were found unilaterally in 27 (22.9%) and bilaterally in 9 (7.6%). Twelve-month follow-up data were available for 113 (95.8%) patients. Forty-six (39%) patients were dead or severely disabled (modified Rankin Scale scores, 5–6), of whom 40 (33.9%) patients had died. Forty-two (35.6%) patients were independent (modified Rankin Scale scores, 0–2). Coma (odds ratio, 2.39 [95% CI, 1.03–5.56]) and fixed dilated pupil (odds ratio, 2.22 [95% CI, 0.90–4.92]) were predictors of death or severe disability. Of the survivors, 56 (78.9%) patients and 61 (87.1%) caregivers expressed a positive opinion on surgery. CONCLUSIONS: Two-thirds of patients with severe CVT were alive and more than one-third were independent 1 year after decompressive surgery. Among survivors, surgery was judged as worthwhile by 4 out of 5 patients and caregivers. These results support the recommendation to perform decompressive neurosurgery in patients with CVT with impending brain herniation.
Keywords: brain; caregivers; hemorrhage; ischemic stroke; stroke